Traces of J.B. Jackson : the man who taught us to see everyday America - Horowitz, Helen Lefkowitz (Midcentury (Charlottesville, Va.), 2020)
"Through a series of biographical essays, this book explores the life of writer, editor, artist, and teacher J. B. Jackson (1909-1996), a man who transformed how Americans understand the landscape, a word he defined as land shaped by human presence. Jackson focused on what he regarded as the essential American landscape, the everyday places of the countryside and city, exploring them as texts that reveal important truths about society and culture, present and past. In his words, landscape is "History made visible." After a varied life that included travel, writing, sketching, ranch labor, and important service in army intelligence in World War II, Jackson moved to New Mexico and single-handedly created the magazine Landscape. As it grew in the years under his direction, 1951-68, Landscape attracted a wide range of contributors. Invitations to lecture and teach followed. For a decade, beginning in the late 1960s, Jackson pioneered the field of landscape studies at Berkeley, Harvard, and elsewhere, mentoring many who later became important architects, planners, and scholars. Jackson was a fascinating person to know. Through friendship as well as writings, he profoundly influenced the lives of many, including my own. Jackson's legacy continues through anthologized collections of his many remarkable works"--